2022
DOI: 10.5539/ijbm.v17n3p93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competitive Strategies on Firm Performance and Mediating Role of Product Innovation

Abstract: The aim of the study is to investigate the effect of competition strategies and product innovation on firm performance and to examine the mediating role of product innovation in relation between competitive strategies and firm performance. One of quantitative methods questionnaire technique was used to test the proposed theoretical model. The research sample 225 enterprises which was listed in Istanbul Chamber of Industry (ISO) The data collection process was completed in June-July-August 2021. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…At present, the focus of the research has been shifted from the "whether influence or not" to "the way and mechanism of influence". Empirical studies have shown that there is positive and complex relation [1,2]. Scholars in contingency strategic management area show that the environment has a moderating effect on the relationship between competitive strategy and firm performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the focus of the research has been shifted from the "whether influence or not" to "the way and mechanism of influence". Empirical studies have shown that there is positive and complex relation [1,2]. Scholars in contingency strategic management area show that the environment has a moderating effect on the relationship between competitive strategy and firm performance [3].…”
Section: Introductionmentioning
confidence: 99%